Largely enhanced piezoelectric and luminescent properties of Er doped BST ceramics. Issue 111 (27th October 2015) - Li, Wei; Xu, Zhijun; Chu, Ruiqing; Wu, Zhihua; Hao, Jigong; Fu, Peng; Du, Juan; Yue, Zhenxing
Abstract : Multifunctional Ba1− x Ti0.96 Sn0.04 O3 + x mol% Er (BST-Er) ceramics were prepared using a solid state reaction method. Abstract : Multifunctional Ba1− x Ti0.96 Sn0.04 O3 + x mol% Er (BST-Er) ceramics were prepared using a solid state reaction method. The large piezoelectric coefficient ( d 33 = 400 pC N −1 ) and field induced strain ( S = 0.175%) were obtained for the BST-Er ceramics at x = 0.5. The polymorphic phase transitions (PPT) from the orthorhombic phase to the tetragonal phase, which contributes to the high piezoelectricities, was identified at room temperature (RT). There are bright green emission bands centered at 520 and 550 nm in up-conversion (UC) luminescence spectra measured under 980 nm laser excitation, which correspond to the radiative transitions from 2 H11/2 and 4 S3/2 to 4 I15/2, respectively. The fluorescence intensity ratio of green UC emissions at 520 and 550 nm was investigated in the temperature range of 233–413 K. The maximum sensing sensitivity was found to be 0.0033 K −1 . The results reveal that the BST-Er ceramics with simple composition are promising multifunctional sensing materials.